2020
DOI: 10.3390/ijms22010358
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Promotes Gap Junctional Intercellular Communication in Cancer Cells

Abstract: Gap junctions are molecular structures that allow communication between neighboring cells. It has been shown that gap junctional intercellular communication (GJIC) is notoriously reduced in cancer cells compared to their normal counterparts. Ouabain, a plant derived substance, widely known for its therapeutic properties on the heart, has been shown to play a role in several types of cancer, although its mechanism of action is not yet fully understood. Since we have previously shown that ouabain enhances GJIC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, there is a growing acknowledgment of pathological processes involving NKA’s engagement as a receptor, where its interaction with GCs can either instigate or alleviate these conditions. Notably, cancer emerges as a significant focus, with numerous studies underscoring the impact of the GC–NKA interaction on various aspects of cancer progression, such as proliferation [ 182 ], adhesion [ 267 ], intercellular communication via gap junctions [ 268 ], epithelial–mesenchymal transition, and apoptosis [ 269 ]. Additionally, other disorders unrelated to cancer but of considerable interest, such as obesity [ 222 ], hypertension [ 270 ], and metabolic disorders [ 271 ], as well as neurological conditions like epilepsy and Alzheimer’s disease [ 187 , 272 ], have been implicated.…”
Section: Discussion and Perspectivementioning
confidence: 99%

Na+/K+-ATPase: More than an Electrogenic Pump

Contreras,
Torres-Carrillo,
Flores-Maldonado
et al. 2024
IJMS
Self Cite
“…Furthermore, there is a growing acknowledgment of pathological processes involving NKA’s engagement as a receptor, where its interaction with GCs can either instigate or alleviate these conditions. Notably, cancer emerges as a significant focus, with numerous studies underscoring the impact of the GC–NKA interaction on various aspects of cancer progression, such as proliferation [ 182 ], adhesion [ 267 ], intercellular communication via gap junctions [ 268 ], epithelial–mesenchymal transition, and apoptosis [ 269 ]. Additionally, other disorders unrelated to cancer but of considerable interest, such as obesity [ 222 ], hypertension [ 270 ], and metabolic disorders [ 271 ], as well as neurological conditions like epilepsy and Alzheimer’s disease [ 187 , 272 ], have been implicated.…”
Section: Discussion and Perspectivementioning
confidence: 99%

Na+/K+-ATPase: More than an Electrogenic Pump

Contreras,
Torres-Carrillo,
Flores-Maldonado
et al. 2024
IJMS
Self Cite
“…We found that they both induce GJIC, following the same signaling pathways as ouabain does, albeit with distinct sensitivity [75]. Moreover, we have shown that ouabain induces increased GJIC in cell lines derived from different types of cancer [76]. More recently we found, interestingly, that GJIC is also modulated by prostaglandin E2, through a process that, in principle, did not appear to be related to ouabain [30].…”
Section: Discussionmentioning
confidence: 99%